Single-layer nanofiber membrane with directional liquid transmission function and preparation method of single-layer nanofiber membrane
The single-layer nanofiber membrane prepared by electrospinning and ultraviolet irradiation technology solves the problems of complex preparation process and unstable structure in the prior art, and realizes efficient liquid transmission function, which is suitable for a variety of application fields.
Patent Information
- Application Number
- CN202411435545.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-15
- Publication Date
- 2024-12-27
AI Technical Summary
The existing preparation methods of nanofiber membranes have problems such as long preparation processes, complex processes, and unstable structures, making it difficult to achieve a continuous and convenient wettable gradient structure.
The composite nanofiber membrane of polyacrylonitrile and titanium dioxide nanoparticles was prepared by electrospinning technology, and a single-layer nanofiber membrane was formed through perfluoro modification and ultraviolet light irradiation to realize the directional liquid transport function of hydrophobic and hydrophilic layers. .
A single-layer nanofiber membrane with stable structure, high breathability and high filtration efficiency has been obtained. It is suitable for medical protective clothing, air purification and liquid separation fields, and provides new ideas for personal wearable air purifiers.
Smart Images

Figure CN119194838A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of air purification, and specifically discloses a single-layer nanofiber membrane with directional liquid transmission function and a preparation method thereof Background Art
[0002] In nature, many plants and animals exhibit directional water transport. For example, the spindle silk of spiders, the beaks of migratory birds, and vascular plants all exhibit directional water movement under the synergistic effect of shape and wettability gradient. Inspired by these organisms, people have made considerable efforts in designing and developing porous materials for directional water transport, especially to ensure continuous directional water transport while well preventing water penetration in the reverse direction, so as to achieve the effect of moisture absorption and quick drying.
[0003] Yan et al. prepared a new Janus membrane by combining super-hydrophilic polyacrylonitrile (PAN) and hydrophobic (PU) fibers through electrospinning (Journal of colloid and interface science, 2020, 565: 426-435). Xiong et al. prepared polydopamine / polyethylene terephthalate / polyvinylidene fluoride (PDA / PET / PVDF) by continuous electrospinning technology and surface chemical modification, and the obtained Janus membrane maintained asymmetric wettability (Environmental Chemical Engineering, 2022, 10 (5): 108459). However, the above composite form is still a simple two-layer composite, so that the thickness of the hydrophobic surface must be very thin to obtain a certain water conductivity, and the significant wettability difference makes reverse osmosis possible.
[0004] Wettability gradient materials are another hot research object for directional water transport materials. The wettability gradient is actually the wettability that gradually changes over the thickness of the porous material. Patent CN107059251B prepares a moisture-conducting nanofiber multilayer composite membrane with a hydrophilic layer, a flow-conducting layer, and a hydrophobic layer by electrospinning to achieve a gradient design; and Miao et al., based on the Janus wetting structure, create a three-layer fiber membrane with progressive wettability by introducing a transfer layer to achieve stable directional water transport capabilities.
[0005] As can be seen from the above, Janus and wettability gradient materials are widely studied objects of directional water transport materials, and both have their own advantages and limitations. The existing research on nanofiber composite membranes related to the two, although with diverse materials and rich methods, is mainly prepared by composite fiber membranes with two, three or more layers, or using different materials to use their own different wettability to form their gradient changes; or processing their surfaces to give each layer different functional properties. These methods have problems such as long preparation process, complex process, and unstable structure of the prepared fiber membrane. Based on the above shortcomings, it is still a challenge to develop a continuous and convenient method for preparing nanofiber membranes with wettability gradient structures. Summary of the invention
[0006] In order to overcome some application disadvantages of existing nanofiber membranes, the present invention provides a method for preparing a single-layer nanofiber membrane with a directional liquid transmission function.
[0007] A method for preparing a single-layer nanofiber membrane with directional liquid transport function comprises the following steps:
[0008] (1) adding polyacrylonitrile to N,N-dimethylformamide to obtain a spinning solution A1, adding titanium dioxide nanoparticles to N,N-dimethylformamide to obtain a dispersion A2 of titanium dioxide nanoparticles; adding the dispersion A2 to the spinning solution A1 to obtain a spinning solution B1;
[0009] Among them, the average molar weight of polyacrylonitrile molecules is 150,000;
[0010] The titanium dioxide nanoparticles are mixed titanium dioxide, wherein, by mass fraction, anatase titanium dioxide is 75% to 80% and rutile titanium dioxide is 20% to 25%.
[0011] The mass ratio of titanium dioxide nanoparticles to polyacrylonitrile is 1:10 to 1:5.
[0012] (2) The spinning solution B1 was used to prepare a hydrophilic composite nanofiber membrane by an electrospinning method;
[0013] During the electrospinning process, the positive spinning voltage was adjusted to 12-15 kV, the negative spinning voltage was -3 kV, the receiving distance was 12-15 cm, the spinning solution pushing speed was 1.0-1.3 mL / h, and the spinning time was 1-2 h.
[0014] (3) adding a perfluorinated reagent to cyclohexane to obtain a perfluorinated modified solution;
[0015] The perfluorinated reagent is perfluorooctyltrimethoxysilane, and the volume ratio of the perfluorinated modification reagent to the cyclohexane solvent is 1:20 to 1:150.
[0016] (4) immersing the hydrophilic composite nanofiber membrane in a perfluorinated modified solution and sealing it in a dark place for 12 hours, taking it out and drying it to obtain a hydrophobic composite nanofiber membrane;
[0017] (5) The hydrophobic composite nanofiber membrane is placed in a dark, enclosed space, the working distance between the sample surface and the ultraviolet lamp is controlled to be 10 cm, and irradiated under the ultraviolet lamp; according to the thickness of the fiber membrane and the power of the ultraviolet lamp, different irradiation times are set to obtain a nanofiber membrane with directional liquid transport function.
[0018] Among them, the maximum power density of UV light is 330mW / cm 2 .
[0019] The nanofiber membrane with directional liquid transmission function prepared by the method of the present invention is a nanofiber membrane with a single-layer structure.
[0020] The single-layer nanofiber membrane with directional liquid transmission function prepared by the method of the present invention is applied to the fields of medical protective clothing, air purification and liquid separation.
[0021] Beneficial effects of the present invention:
[0022] The present invention uses electrospinning technology to prepare an electrospun single-layer nanofiber membrane, using polyacrylonitrile as the flexible skeleton of the fiber layer, and increasing the active sites of polyacrylonitrile fibers by loading titanium dioxide nanoparticles, while giving the fiber membrane characteristics such as ultraviolet absorption and photocatalysis; the fiber-loaded nanoparticles construct a micro-nano structure to increase the roughness of the fiber membrane surface, and then treat the fiber membrane with a perfluorinated solution with low surface energy properties, so that the perfluorinated functional groups are combined with the surface of the titanium dioxide particles on the fiber membrane, and the hydrophobic properties of the nanofiber membrane are jointly improved; then the fiber membrane is irradiated with ultraviolet light in a dark environment, and the irradiation time is controlled; the composite nanofiber membrane finally obtained has good unidirectional moisture conduction ability, good air permeability, high filtration efficiency and other characteristics. This functional electrospun nanofiber membrane can provide new ideas for the research and development of personal wearable air purifiers. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the technical solution of the embodiment of the present invention, the following briefly introduces the drawings required for describing the embodiment, wherein:
[0024] Figure 1 The figure is a schematic diagram of the preparation process of the single-layer nanofiber membrane with directional liquid transport function of the present invention.
[0025] Figure 2 These are scanning electron microscope images of PAN, TiO2 / PAN, and F-TiO2 / PAN fiber membranes prepared in Comparative Examples 1 to 2 and Example 2 of the present invention.
[0026] Figure 3 This is the XRD curve diagram of PAN, F-TiO2 / PAN fiber membrane and raw material titanium dioxide nanoparticles prepared in Comparative Example 1 and Example 2 of the present invention.
[0027] Figure 4 This is the infrared spectra of the electrospun nanofiber membranes of PAN and F-TiO2 / PAN prepared in Comparative Example 1 and Example 2 of the present invention before and after irradiation with ultraviolet light.
[0028] Figure 5 These are the thermogravimetric curves of PAN, TiO2 / PAN, and F-TiO2 / PAN fiber membranes prepared in Comparative Examples 1 to 2 and Example 2 of the present invention.
[0029] Figure 6 The water contact angles of different sides of the F-TiO2 / PAN fiber membrane prepared in Example 2 of the present invention after being irradiated with ultraviolet light.
[0030] Figure 7 The wetting conditions of water droplets on different side surfaces of the F-TiO2 / PAN fiber membrane prepared in Example 2 of the present invention after being irradiated with ultraviolet light.
[0031] Figure 8 The pore size distribution of the F-TiO2 / PAN fiber membrane prepared in Example 2 of the present invention (average 1.11 μm) and the gas flux of 455 m 3 ·m -2 ·h -1 kPa -1 .
[0032] Fig. 9 The air purification efficiency and pressure drop test results of the F-TiO2 / PAN fiber membrane prepared in Example 2 of the present invention show that the air purification efficiency reaches 99.6% and the pressure drop is 78Pa. DETAILED DESCRIPTION
[0033] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.
[0034] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0035] The raw materials in the examples of the present invention are all commercially available unless otherwise specified, as shown in Table 1.
[0036] Table 1
[0037]
[0038] Example 1
[0039] (1) Preparation of spinning solution:
[0040] 0.9 g of polyacrylonitrile was added to 6.0 g of N,N-dimethylformamide, and the mixture was magnetically stirred at room temperature for 5 hours at a rotation speed of 300 rpm to obtain a spinning solution A1;
[0041] 0.14 g of titanium dioxide nanoparticles were added to 2.0 g of N,N-dimethylformamide, and then ultrasonicated at a power of 100 W for 0.5 hour and magnetically stirred at room temperature for 12 hours to uniformly disperse the particles, thereby obtaining a dispersion A2 of titanium dioxide nanoparticles;
[0042] Dispersion A2 was added to spinning solution A1, magnetically stirred at room temperature for 2 hours, ultrasonicated for 2 hours, and then magnetically stirred for 8 hours to evenly disperse the nanoparticles, to obtain spinning solution B1 with a PAN mass concentration of 10% and a mass ratio of titanium dioxide nanoparticles to PAN of 7:45.
[0043] (2) Preparation of nanocomposite fiber membrane:
[0044] The spinning solution B1 was injected into a 5 mL syringe, and the electrospinning method was used to adjust the spinning positive voltage to 13 kV, the spinning negative voltage to -3 kV, the receiving distance to 12 cm, the spinning solution pushing speed to 1.3 mL / h, and the spinning time to 1 h to prepare a hydrophilic composite nanofiber membrane.
[0045] (3) Preparation of hydrophobic composite nanofiber membrane: add 0.5 mL of perfluorooctyltrimethoxysilane to 50 mL of cyclohexane solution, and stir magnetically at room temperature at a speed of 300 rpm for 10 minutes to obtain a perfluoro-modified solution; immerse the hydrophilic composite nanofiber membrane prepared above in the perfluoro-modified solution, seal and immerse for 12 hours in a light-proof manner, take out the fiber membrane and dry it in an oven at 60°C for 2 hours to obtain a hydrophobic composite nanofiber membrane with a thickness of 50 μm.
[0046] (4) Regulation of directional liquid transport function:
[0047] The hydrophobic composite nanofiber membrane prepared in step (3) was placed in a dark, enclosed space, and the working distance between the sample surface and the ultraviolet lamp was controlled to be 10 cm, and the wavelength was 365 nm and the power was 220 mW / cm 2 After irradiation under ultraviolet light for 12 minutes, a nanofiber membrane with directional liquid transport function can be obtained.
[0048] Example 2
[0049] (1) Preparation of spinning solution:
[0050] 1.2 g of polyacrylonitrile was added to 6.0 g of N,N-dimethylformamide, and the mixture was magnetically stirred at room temperature for 5 hours at a rotation speed of 300 rpm to obtain a spinning solution A1;
[0051] 0.18 g of titanium dioxide nanoparticles were added to 2.0 g of N,N-dimethylformamide, and the mixture was ultrasonicated at a power of 100 W for 0.5 hours and then magnetically stirred at room temperature for 12 hours to disperse the particles uniformly, thereby obtaining a dispersion A2 of titanium dioxide nanoparticles.
[0052] Dispersion A2 was added to spinning solution A1, magnetically stirred at room temperature for 2 hours, ultrasonicated for 2 hours, and then magnetically stirred for 8 hours to evenly disperse the nanoparticles, to obtain spinning solution B1 with a PAN mass concentration of 12.8% and a mass ratio of titanium dioxide nanoparticles to PAN of 3:20.
[0053] (2) Preparation of nanocomposite fiber membrane:
[0054] The spinning solution B1 was injected into a 5 mL syringe, and the electrospinning method was used to adjust the spinning positive voltage to 13 kV, the spinning negative voltage to -3 kV, the receiving distance to 12 cm, the spinning solution pushing speed to 1.3 mL / h, and the spinning time to 1 h to prepare a hydrophilic composite nanofiber membrane.
[0055] (3) Preparation of hydrophobic composite nanofiber membrane: add 0.5 mL of perfluorooctyltrimethoxysilane to 50 mL of cyclohexane solution, and stir magnetically at room temperature at 300 rpm for 10 minutes to obtain a perfluoro-modified solution; immerse the hydrophilic composite nanofiber membrane prepared above in the perfluoro-modified solution, seal and immerse for 12 hours in a light-proof manner, take out the fiber membrane and dry it in an oven at 60°C for 2 hours to obtain a hydrophobic composite nanofiber membrane with a thickness of 50 μm.
[0056] (4) Regulation of directional liquid transport function:
[0057] The hydrophobic composite nanofiber membrane prepared in step (3) was placed in a dark, enclosed space, and the working distance between the sample surface and the ultraviolet lamp was controlled to be 10 cm, and the wavelength was 365 nm and the power was 220 mW / cm 2 After irradiation under ultraviolet light for 12 minutes, a nanofiber membrane with directional liquid transport function can be obtained.
[0058] Example 3
[0059] (1) Preparation of spinning solution:
[0060] 1.4 g of polyacrylonitrile was added to 6.0 g of N,N-dimethylformamide, and the mixture was magnetically stirred at room temperature for 5 hours at a rotation speed of 300 rpm to obtain a spinning solution A1;
[0061] 0.21 g of titanium dioxide nanoparticles were added to 2.0 g of N,N-dimethylformamide, and then ultrasonicated at a power of 100 W for 0.5 hour and magnetically stirred at room temperature for 12 hours to uniformly disperse the particles, thereby obtaining a dispersion A2 of titanium dioxide nanoparticles;
[0062] Dispersion A2 was added to spinning solution A1, magnetically stirred at room temperature for 2 hours, ultrasonicated for 2 hours, and then magnetically stirred for 8 hours to evenly disperse the nanoparticles, to obtain spinning solution B1 with a PAN mass concentration of 14.6% and a mass ratio of titanium dioxide nanoparticles to PAN of 3:20.
[0063] (2) Preparation of nanocomposite fiber membrane:
[0064] The spinning solution B1 was injected into a 5 mL syringe, and the electrospinning method was used to adjust the spinning positive voltage to 13 kV, the spinning negative voltage to -3 kV, the receiving distance to 12 cm, the spinning solution pushing speed to 1.3 mL / h, and the spinning time to 1 h to prepare a hydrophilic composite nanofiber membrane.
[0065] (3) Preparation of hydrophobic composite nanofiber membrane: add 0.5 mL of perfluorooctyltrimethoxysilane to 50 mL of cyclohexane solution, and stir magnetically at room temperature at 300 rpm for 10 minutes to obtain a perfluoro-modified solution; immerse the hydrophilic composite nanofiber membrane prepared above in the perfluoro-modified solution, seal and immerse for 12 hours in a light-proof manner, take out the fiber membrane and dry it in an oven at 60°C for 2 hours to obtain a hydrophobic composite nanofiber membrane with a thickness of 50 μm.
[0066] (4) Regulation of directional liquid transport function:
[0067] The hydrophobic composite nanofiber membrane prepared in step (3) was placed in a dark, enclosed space, and the working distance between the sample surface and the ultraviolet lamp was controlled to be 10 cm, and the wavelength was 365 nm and the power was 220 mW / cm 2 After irradiation under ultraviolet light for 12 minutes, a nanofiber membrane with directional liquid transport function can be obtained.
[0068] Example 4
[0069] (1) Preparation of spinning solution:
[0070] 1.2 g of polyacrylonitrile was added to 6.0 g of N,N-dimethylformamide, and the mixture was magnetically stirred at room temperature for 5 hours at a rotation speed of 300 rpm to obtain a spinning solution A1;
[0071] 0.12 g of titanium dioxide nanoparticles were added to 2.0 g of N,N-dimethylformamide, and then ultrasonicated at a power of 100 W for 0.5 hour and magnetically stirred at room temperature for 12 hours to uniformly disperse the particles, thereby obtaining a dispersion A2 of titanium dioxide nanoparticles;
[0072] Dispersion A2 was added to spinning solution A1, magnetically stirred at room temperature for 2 hours, ultrasonicated for 2 hours, and then magnetically stirred for 8 hours to evenly disperse the nanoparticles, to obtain spinning solution B1 with a PAN mass concentration of 12.9% and a mass ratio of titanium dioxide nanoparticles to PAN of 1:10.
[0073] (2) Preparation of nanocomposite fiber membrane:
[0074] The spinning solution B1 was injected into a 5 mL syringe, and the electrospinning method was used to adjust the spinning positive voltage to 13 kV, the spinning negative voltage to -3 kV, the receiving distance to 12 cm, the spinning solution pushing speed to 1.3 mL / h, and the spinning time to 1 h to prepare a hydrophilic composite nanofiber membrane.
[0075] (3) Preparation of hydrophobic composite nanofiber membrane: add 0.5 mL of perfluorooctyltrimethoxysilane to 50 mL of cyclohexane solution, and stir magnetically at room temperature at a speed of 300 rpm for 10 minutes to obtain a perfluoro-modified solution; immerse the hydrophilic composite nanofiber membrane prepared above in the perfluoro-modified solution, seal and immerse for 12 hours in a light-proof manner, take out the fiber membrane and dry it in an oven at 60°C for 2 hours to obtain a hydrophobic composite nanofiber membrane with a thickness of 50 μm.
[0076] (4) Regulation of directional liquid transport function:
[0077] The hydrophobic composite nanofiber membrane prepared in step (3) was placed in a dark, enclosed space, and the working distance between the sample surface and the ultraviolet lamp was controlled to be 10 cm, and the wavelength was 365 nm and the power was 220 mW / cm 2 After irradiation under ultraviolet light for 12 minutes, a nanofiber membrane with directional liquid transport function can be obtained.
[0078] Example 5
[0079] (1) Preparation of spinning solution:
[0080] 1.2 g of polyacrylonitrile was added to 6.0 g of N,N-dimethylformamide, and the mixture was magnetically stirred at room temperature for 5 hours at a rotation speed of 300 rpm to obtain a spinning solution A1;
[0081] 0.24 g of titanium dioxide nanoparticles were added to 2.0 g of N,N-dimethylformamide, and then ultrasonicated at a power of 100 W for 0.5 hour and magnetically stirred at room temperature for 12 hours to uniformly disperse the particles, thereby obtaining a dispersion A2 of titanium dioxide nanoparticles;
[0082] Dispersion A2 was added to spinning solution A1, magnetically stirred at room temperature for 2 hours, ultrasonicated for 2 hours, and then magnetically stirred for 8 hours to evenly disperse the nanoparticles, to obtain spinning solution B1 with a PAN mass concentration of 12.7% and a mass ratio of titanium dioxide nanoparticles to PAN of 1:5.
[0083] (2) Preparation of nanocomposite fiber membrane:
[0084] The spinning solution B1 was injected into a 5 mL syringe, and the electrospinning method was used to adjust the spinning positive voltage to 13 kV, the spinning negative voltage to -3 kV, the receiving distance to 12 cm, the spinning solution pushing speed to 1.3 mL / h, and the spinning time to 1 h to prepare a hydrophilic composite nanofiber membrane.
[0085] (3) Preparation of hydrophobic composite nanofiber membrane: add 0.5 mL of perfluorooctyltrimethoxysilane to 50 mL of cyclohexane solution, and stir magnetically at room temperature at a speed of 300 rpm for 10 minutes to obtain a perfluoro-modified solution; immerse the hydrophilic composite nanofiber membrane prepared above in the perfluoro-modified solution, seal and immerse for 12 hours in a light-proof manner, take out the fiber membrane and dry it in an oven at 60°C for 2 hours to obtain a hydrophobic composite nanofiber membrane with a thickness of 50 μm.
[0086] (4) Regulation of directional liquid transport function:
[0087] The hydrophobic composite nanofiber membrane prepared in step (3) was placed in a dark, enclosed space, and the working distance between the sample surface and the ultraviolet lamp was controlled to be 10 cm, and the wavelength was 365 nm and the power was 220 mW / cm 2 After irradiation under ultraviolet light for 12 minutes, a nanofiber membrane with directional liquid transport function can be obtained.
[0088] Example 6
[0089] (1) The spinning solution was prepared in the same manner as in Example 2.
[0090] (2) Preparation of nanocomposite fiber membrane:
[0091] The spinning solution B1 was injected into a 5 mL syringe, and the hydrophilic composite nanofiber membrane was prepared by adjusting the spinning positive voltage to 13 kV, the spinning negative voltage to -3 kV, the receiving distance to 12 cm, the spinning solution pushing speed to 1.3 mL / h, and the spinning time to 2 h through the electrospinning method.
[0092] (3) Preparation of hydrophobic composite nanofiber membrane: add 0.5 mL of perfluorooctyltrimethoxysilane to 50 mL of cyclohexane solution, and stir magnetically at room temperature at a speed of 300 rpm for 10 minutes to obtain a perfluoro-modified solution; immerse the hydrophilic composite nanofiber membrane prepared above in the perfluoro-modified solution, seal and immerse for 12 hours in a light-proof manner, take out the fiber membrane and dry it in an oven at 60°C for 2 hours to obtain a hydrophobic composite nanofiber membrane with a thickness of 90 μm.
[0093] (4) Regulation of directional liquid transport function:
[0094] The hydrophobic composite nanofiber membrane prepared in step (3) was placed in a dark, enclosed space, and the working distance between the sample surface and the ultraviolet lamp was controlled to be 10 cm, and the wavelength was 365 nm and the power was 220 mW / cm 2 After irradiation under ultraviolet light for 16 minutes, a nanofiber membrane with directional liquid transport function can be obtained.
[0095] Example 7
[0096] (1) The spinning solution was prepared in the same manner as in Example 2.
[0097] (2) The preparation of nanocomposite fiber membrane is the same as that in Example 2.
[0098] (3) Preparation of hydrophobic composite nanofiber membrane: add 0.5 mL of perfluorooctyltrimethoxysilane to 50 mL of cyclohexane solution, and stir magnetically at room temperature at a speed of 300 rpm for 10 minutes to obtain a perfluoro-modified solution; immerse the hydrophilic composite nanofiber membrane prepared above in the perfluoro-modified solution, seal and immerse for 12 hours in a light-proof manner, take out the fiber membrane and dry it in an oven at 60°C for 2 hours to obtain a hydrophobic composite nanofiber membrane with a thickness of 50 μm.
[0099] (4) Regulation of directional liquid transport function:
[0100] The hydrophobic composite nanofiber membrane prepared in step (3) was placed in a dark, enclosed space, and the working distance between the sample surface and the ultraviolet lamp was controlled to be 10 cm, and the wavelength was 365 nm and the power was 330 mW / cm 2 After irradiation under ultraviolet light for 9 minutes, a nanofiber membrane with directional liquid transport function can be obtained.
[0101] Example 8
[0102] (1) The spinning solution was prepared in the same manner as in Example 2.
[0103] (2) The preparation of nanocomposite fiber membrane is the same as that in Example 2.
[0104] (3) Preparation of hydrophobic composite nanofiber membrane: add 2.5 mL of perfluorooctyltrimethoxysilane to 50 mL of cyclohexane solution, and stir magnetically at room temperature at a speed of 300 rpm for 10 minutes to obtain a perfluorinated modified solution; immerse the hydrophilic composite nanofiber membrane prepared above in the perfluorinated modified solution, seal and immerse for 12 hours in a light-proof manner, take out the fiber membrane and dry it in an oven at 60°C for 2 hours to obtain a hydrophobic composite nanofiber membrane with a thickness of 50 μm.
[0105] (4) Regulation of directional liquid transport function:
[0106] The hydrophobic composite nanofiber membrane prepared in step (3) was placed in a dark, enclosed space, and the working distance between the sample surface and the ultraviolet lamp was controlled to be 10 cm, and the wavelength was 365 nm and the power was 220 mW / cm 2 After irradiation under ultraviolet light for 12 minutes, a nanofiber membrane with directional liquid transport function can be obtained.
[0107] Example 9
[0108] (1) The spinning solution was prepared in the same manner as in Example 2.
[0109] (2) The preparation of nanocomposite fiber membrane is the same as that in Example 2.
[0110] (3) Preparation of hydrophobic composite nanofiber membrane: add 1.0 mL of perfluorooctyltrimethoxysilane to 50 mL of cyclohexane solution, and stir magnetically at room temperature at 300 rpm for 10 minutes to obtain a perfluoro-modified solution; immerse the hydrophilic composite nanofiber membrane prepared above in the perfluoro-modified solution, seal and immerse for 12 hours in a light-proof chamber, take out the fiber membrane and dry it in an oven at 60°C for 2 hours to obtain a hydrophobic composite nanofiber membrane with a thickness of 50 μm.
[0111] (4) Regulation of directional liquid transport function:
[0112] The hydrophobic composite nanofiber membrane prepared in step (3) was placed in a dark, enclosed space, and the working distance between the sample surface and the ultraviolet lamp was controlled to be 10 cm, and the wavelength was 365 nm and the power was 220 mW / cm 2 After irradiation under ultraviolet light for 12 minutes, a nanofiber membrane with directional liquid transport function can be obtained.
[0113] Example 10
[0114] (1) The spinning solution was prepared in the same manner as in Example 2.
[0115] (2) The preparation of nanocomposite fiber membrane is the same as that in Example 2.
[0116] (3) Preparation of hydrophobic composite nanofiber membrane: add 0.33 mL of perfluorooctyltrimethoxysilane to 50 mL of cyclohexane solution, and stir magnetically at room temperature at a speed of 300 rpm for 10 minutes to obtain a perfluoro-modified solution; immerse the hydrophilic composite nanofiber membrane prepared above in the perfluoro-modified solution, seal and immerse for 12 hours in a light-proof manner, take out the fiber membrane and dry it in an oven at 60°C for 2 hours to obtain a hydrophobic composite nanofiber membrane with a thickness of 50 μm.
[0117] (4) Regulation of directional liquid transport function:
[0118] The hydrophobic composite nanofiber membrane prepared in step (3) was placed in a dark, enclosed space, and the working distance between the sample surface and the ultraviolet lamp was controlled to be 10 cm, and the wavelength was 365 nm and the power was 220 mW / cm 2 After irradiation under ultraviolet light for 12 minutes, a nanofiber membrane with directional liquid transport function can be obtained.
[0119] Comparative Example 1
[0120] The difference from Example 2 is that no titanium dioxide nanoparticles are added, and no modification or light treatment is performed.
[0121] (1) Preparation of spinning solution:
[0122] 1.2 g of polyacrylonitrile was added to 8.0 g of N,N-dimethylformamide, and the mixture was magnetically stirred at room temperature for 5 hours at a rotation speed of 300 rpm to obtain a spinning solution A1;
[0123] (2) Preparation of nanocomposite fiber membrane:
[0124] The spinning solution A1 was injected into a 5 mL syringe, and the hydrophilic composite nanofiber membrane was prepared by adjusting the spinning positive voltage to 13 kV, the spinning negative voltage to -3 kV, the receiving distance to 12 cm, the spinning solution pushing speed to 1.3 mL / h, and the spinning time to 1 h through the electrospinning method.
[0125] Comparative Example 2
[0126] The difference from Example 2 is that the TiO2 / PAN nanofiber membrane is not modified.
[0127] (1) Preparation of spinning solution:
[0128] 1.2 g of polyacrylonitrile was added to 6.0 g of N,N-dimethylformamide, and the mixture was magnetically stirred at room temperature for 5 hours at a rotation speed of 300 rpm to obtain a spinning solution A1;
[0129] 0.18 g of titanium dioxide nanoparticles were added to 2.0 g of N,N-dimethylformamide, and the mixture was ultrasonicated at a power of 100 W for 0.5 hours and then magnetically stirred at room temperature for 12 hours to disperse the particles uniformly, thereby obtaining a dispersion A2 of titanium dioxide nanoparticles.
[0130] The dispersion A2 was added into the spinning solution A1, magnetically stirred at room temperature for 2 hours, ultrasonicated for 2 hours, and then magnetically stirred for 8 hours to uniformly disperse the nanoparticles, to obtain the spinning solution B1.
[0131] (2) Preparation of nanocomposite fiber membrane:
[0132] The spinning solution B1 was injected into a 5 mL syringe, and the electrospinning method was used to adjust the spinning positive voltage to 13 kV, the spinning negative voltage to -3 kV, the receiving distance to 12 cm, the spinning solution pushing speed to 1.3 mL / h, and the spinning time to 1 h to prepare a hydrophilic composite nanofiber membrane.
[0133] Comparative Example 3
[0134] The difference from Example 2 is that the TiO2 / PAN nanofiber membrane is not irradiated with ultraviolet light.
[0135] (1) Preparation of spinning solution:
[0136] 1.2 g of polyacrylonitrile was added to 6.0 g of N,N-dimethylformamide, and the mixture was magnetically stirred at room temperature for 5 hours at a rotation speed of 300 rpm to obtain a spinning solution A1;
[0137] 0.18 g of titanium dioxide nanoparticles were added to 2.0 g of N,N-dimethylformamide, and the mixture was ultrasonicated at a power of 100 W for 0.5 hours and then magnetically stirred at room temperature for 12 hours to disperse the particles uniformly, thereby obtaining a dispersion A2 of titanium dioxide nanoparticles.
[0138] The dispersion A2 was added into the spinning solution A1, magnetically stirred at room temperature for 2 hours, ultrasonicated for 2 hours, and then magnetically stirred for 8 hours to uniformly disperse the nanoparticles, to obtain the spinning solution B1.
[0139] (2) Preparation of nanocomposite fiber membrane:
[0140] The spinning solution B1 was injected into a 5 mL syringe, and the hydrophilic composite nanofiber membrane was prepared by adjusting the spinning positive voltage to 13 kV, the spinning negative voltage to -3 kV, the receiving distance to 12 cm, the spinning solution pushing speed to 1.3 mL / h, and the spinning time to 1 h through the electrospinning method.
[0141] (3) Preparation of hydrophobic composite nanofiber membrane: add 0.5 mL of perfluorooctyltrimethoxysilane to 50 mL of cyclohexane solution, and stir magnetically at room temperature at 300 rpm for 10 minutes to obtain a perfluoro-modified solution; immerse the hydrophilic composite nanofiber membrane prepared above in the perfluoro-modified solution, seal and protect from light for 12 hours, take out the fiber membrane and dry it in an oven at 60°C for 2 hours to obtain a hydrophobic composite nanofiber membrane.
[0142] Experimental example
[0143] The morphologies of the PAN, TiO2 / PAN, and F-TiO2 / PAN electrospun nanofiber membranes prepared in Comparative Examples 1 to 2 and Example 2 are shown in the attached figure. Figure 2 As shown, the surface of PAN nanofiber is smooth; after adding titanium dioxide nanoparticles, the nanoparticles are loaded on the surface of TiO2 / PAN fiber, forming a micro-nano structure on the fiber surface; it is modified by immersing it in a perfluorinated solution, and the hydroxyl groups on the surface of titanium dioxide are combined with the perfluorinated groups of the perfluorinated reagent, thereby improving the hydrophobicity of the fiber membrane.
[0144] The XRD spectra of PAN, F-TiO2 / PAN electrospun nanofiber membranes and raw material titanium dioxide nanoparticles prepared in Comparative Example 1 and Example 2 are shown in the attached figure. Figure 3 As shown, the characteristic peaks of titanium dioxide nanoparticles and PAN fiber membrane can be observed one-to-one on the F-TiO2 / PAN electrospun nanofiber membrane, indicating that titanium dioxide nanoparticles are successfully doped on the fiber membrane.
[0145] The infrared spectra of the electrospun nanofiber membranes of PAN and F-TiO2 / PAN obtained in Comparative Example 1 and Example 2 before and after irradiation with ultraviolet light are shown in the attached figure. Figure 4 As shown in the figure, it can be seen that the F-TiO2 / PAN fiber membrane has a characteristic peak of -CF, which disappears after being irradiated by ultraviolet light, indicating the successful preparation of the modified fiber membrane and the effect of ultraviolet light irradiation.
[0146] The thermal weight loss curves of PAN, TiO2 / PAN, and F-TiO2 / PAN electrospun nanofiber membranes prepared in Comparative Examples 1-2 and Example 2 are shown in the attached figure. Figure 5 As shown in the figure, it can be seen that after the fiber membrane is modified, the fiber membrane can be kept stable within 200°C.
[0147] The F-TiO2 / PAN electrospun nanofiber membrane prepared in Example 2 above showed a great difference in wettability on both sides after being irradiated by ultraviolet light. Figure 6 As shown in the figure, after being irradiated by ultraviolet light, the irradiated surface of the nanofiber membrane is hydrophilic, while the back side remains hydrophobic. Figure 7 As shown, water droplets on the hydrophobic side can be transferred to the hydrophilic side, but not vice versa.
[0148] The F-TiO2 / PAN electrospun nanofiber membrane prepared in Example 2 was tested for NaCl aerosol filtration performance using an automatic filter material tester. The air purification efficiency and pressure drop results are shown in Figure 2. Fig. 9 As shown. The air purification efficiency of F-TiO2 / PAN nanofiber membrane reaches 99.6%, and the resistance is 78Pa; it can be seen that F-TiO2 / PAN electrospun nanofiber membrane exhibits good air purification performance.
[0149] The present invention uses electrospinning technology to prepare a composite nanofiber membrane of polyacrylonitrile and titanium dioxide nanoparticles, and the surface of the composite nanofiber membrane is completely hydrophilic on one side and completely hydrophobic on the other side, which can effectively achieve unidirectional moisture conduction of water vapor, effectively filter tiny particulate pollutants, and has high filtration efficiency. The nanofiber membrane that can unidirectionally transmit water vapor to improve wearing comfort has good application prospects in the field of personal wearable air purifiers.
[0150] Table 2 Water contact angle of the examples
[0151]
[0152] Table 3 Water contact angle of comparative examples
[0153]
[0154] The present invention combines electrospinning and ultraviolet irradiation technology to prepare a directional liquid transport nanofiber membrane. The preparation process is simple and continuous. The hydrophobic layer, the guide layer and the hydrophilic layer can be integrated through ultraviolet irradiation without the need for external force connection. The fiber membrane has higher integrity and a more stable structure.
Claims
1. A method for preparing a single-layer nanofiber membrane with directional liquid transport function, characterized in that: The preparation method steps are as follows: (1) adding polyacrylonitrile to N,N-dimethylformamide to obtain a spinning solution A1, and adding titanium dioxide nanoparticles to N,N-dimethylformamide to obtain a dispersion A2 of titanium dioxide nanoparticles; (2) adding the dispersion A2 to the spinning solution A1 to obtain the spinning solution B1; and preparing the hydrophilic composite nanofiber membrane from the spinning solution B1 by an electrospinning method; (3) adding a perfluorinated reagent to cyclohexane to obtain a perfluorinated modified solution; (4) immersing the hydrophilic composite nanofiber membrane in a perfluorinated modified solution and sealing it in a dark place for 12 hours, taking it out and drying it to obtain a hydrophobic composite nanofiber membrane; (5) Placing the hydrophobic composite nanofiber membrane in a dark, enclosed space and irradiating it under ultraviolet light to obtain a single-layer nanofiber membrane with directional liquid transport function.
2. The method for preparing a single-layer nanofiber membrane with directional liquid transport function according to claim 1, characterized in that: The average molar weight of the polyacrylonitrile molecules is 150,000.
3. The method for preparing a single-layer nanofiber membrane with directional liquid transport function according to claim 1, characterized in that: The titanium dioxide nanoparticles are mixed titanium dioxide, wherein, by mass fraction, anatase titanium dioxide is 75% to 80% and rutile titanium dioxide is 20% to 25%.
4. The method for preparing a single-layer nanofiber membrane with directional liquid transport function according to claim 1, characterized in that: The mass ratio of N,N-dimethylformamide in spinning solutions A1 and A2 is 3:
1.
5. The method for preparing a single-layer nanofiber membrane with directional liquid transport function according to claim 1, characterized in that: The mass ratio of the titanium dioxide nanoparticles to polyacrylonitrile is 1:10 to 1:
5.
6. The method for preparing a single-layer nanofiber membrane with directional liquid transport function according to claim 1, characterized in that: The electrospinning is performed by adjusting the positive spinning voltage to 12-15 kV, the negative spinning voltage to -3 kV, the receiving distance to 12-15 cm, the spinning solution pushing speed to 1.0-1.3 mL / h, and the spinning time to 1-2 h.
7. The method for preparing a single-layer nanofiber membrane with directional liquid transport function according to claim 1, characterized in that: The perfluorinated reagent is perfluorooctyltrimethoxysilane; the volume ratio of the perfluorinated modification reagent to cyclohexane is 1:20 to 1:
150.
8. The method for preparing a single-layer nanofiber membrane with directional liquid transport function according to claim 1, characterized in that: When the UV lamp is used for irradiation, the working distance between the sample surface and the UV lamp is 10 cm, and the maximum power density of the UV lamp is 330 mW / cm 2 .
9. A single-layer nanofiber membrane with directional liquid transport function obtained by the preparation method according to any one of claims 1 to 8.
10. The single-layer nanofiber membrane with directional liquid transport function as claimed in claim 9 is used in the fields of air purification, medical protective clothing, and liquid separation.
Citation Information
Patent Citations
Preparation method of unidirectional hygroscopic nanofiber multilayer composite membrane with wetting gradient
CN107059251B
Cited By
Nanofiber membrane with gradient wettability pore structure and preparation method thereof
CN120001229A
